Gender faces in the textbook of Al-‘Arabiyyah li al-Nāsyi’īn: A critical discourse analysis study - Shifany Maulida Hijjah; Razik Insani; Ahmad Royani; Achmad Fudhaili (An-Nisa’ Journal of Gender Studies, 2024)
The polemic of gender equality and justice in its status and role in society is one of the studies that is often echoed to this day. Polemics over gender equality can be found in various fields, one of which is in the field of education, especially in the learning media, namely textbooks. This study examines women’s subordination, activity-based gender stereotypes, and cultural codes used to normalize gender roles and shape readers’ ideological understanding in the Arabic textbook Al-Arabiyah li al-Nasyi'in.  This study employs a qualitative approach using library research to analyze the Arabic textbook Al-'Arabiyah li al-Nasyi'in Volume 2 through Sara Mills’ critical discourse analysis framework. This study reveals three findings: (1) the subordination of women in the text through domestic roles, while men are associated with outdoor activities and greater dominance; (2) gender stereotypes in the text, with feminine labels assigned to women and masculine labels to men through garden and car activities; and (3) the author employs mediation and cultural codes to normalize gender roles and engage readers in the construction of ideological meaning. This study concludes that the textbook is not a neutral medium but a reproduction of patriarchy through everyday language, which appears natural and shapes students’ acceptance of gender inequality as something inherent. This study contributes to strengthening Sara Mills’ Critical Discourse Analysis by providing a gender bias detection instrument for teaching materials, thereby promoting inclusive curricula and critical student learning.